Environmental Awareness and Cholinesterase Level of Farmers - Wiboonwipa, Prakai; Thiengkamol, Nongnapas; Thiengkamol, Tanarat Khoowaranyoo (วารสารเกษมบัณฑิต, 2019)
The purpose of this research was to develop model of environmental awareness factors affecting cholinesterase level of agriculturist in Yasothon Province by a survey research and the questionnaire used for data collection from the population of agriculturists in year of 2014. Multi-stage random sampling was employed for sampling sample group of 389 agriculturists from population of 70,546 agriculturist. Structural Equation model (SEM) was used for model verification covering knowledge of pesticide use, knowledge of primary health care, psychological trait, psychological state, environmental education, inspiration of public mind for environmental conservation, and environmental conservation behavior. Research results illustrated that the psychological trait (PST), psychological state (PsS), inspiration of public mind for environmental conservation (INS), environmental education (EE), environmental conservation behavior (BEH), knowledge of primary health care (HK), and knowledge of pesticide use (Kno) affected on cholinesterase level with value of 0.95, 0.92, , 0.88, 0.87, 0.81, 0.77, and 0.76 respectively.